Elmer Fudd's Cellar - Bob; Smith (New York Sterling Publishers, 1992)
ften bumbling attempts to explore and manage the unexpected surprises that await him in the cellar. True to the Looney Tunes spirit, the story is filled with playful antics, comical situations, and the classic charm of the animated series, making it an entertaining read for young fans and a delightful addition to the Looney Tunes collection. ften bumbling attempts to explore and manage the unexpected surprises that await him in the cellar. True to the Looney Tunes spirit, the story is filled with playful antics, comical situations, and the classic charm of the animated series, making it an entertaining read for young fans and a delightful addition to the Looney Tunes collection.